Transmissible Gastroenteritis Virus Infection Up-Regulates FcRn Expression via Nucleocapsid Protein and Secretion of TGF-β in Porcine Intestinal Epithelial Cells - Qian, Shaoju; Gao, Zitong; Cao, Rui; Yang, Kang; Cui, Yijie; Li, Shaowen; Meng, Xianrong; He, Qigai; Li, Zili (Frontiers in Microbiology, 2020)
Transmissible gastroenteritis virus (TGEV) is a porcine intestinal coronavirus that causes fatal severe watery diarrhea in piglets. The neonatal Fc receptor (FcRn) is the only IgG transport receptor; its expression on mucosal surfaces is triggered upon viral stimulation, which significantly enhances mucosal immunity. We utilized TGEV as a model pathogen to explore the role of FcRn in resisting viral invasion and in overall intestinal mucosal immunity. TGEV induced FcRn expression by activating NF-κB signaling in porcine small intestinal epithelial (IPEC-J2) cells, however, the underlying mechanisms are unclear. First, using small interfering RNAs, we found that TGEV up-regulated FcRn expression via TLR3 and TLR9 and RIG-I. Moreover, TGEV induced IL-1β, IL-6, IL-8, TGF-β and TNF-α production. TGF-β-stimulated IPEC-J2 cells highly up-regulated FcRn expression, while treatment with a JNK-specific inhibitor down-regulated the expression. TGEV nucleocapsid (N) protein also enhanced FcRn promoter activity via the NF-κB signaling pathway and its central region (aa 128–252) was essential for FcRn activation. Additionally, N protein-mediated FcRn up-regulation promotes IgG transcytosis. Thus, TGEV N protein and TGF-β up-regulated FcRn expression, further clarifying the molecular mechanism of upregulation of FcRn expression by TGEV.